Mali : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Nonobservance of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper focuses on Mali's First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Nonobservance Performance Criteria. Program implementation in 2004 was mixed. The authorities stuck to their fiscal program, meeting all targets and indicators through end-September, despite some revenue and financing shortfalls. However, progress on structural reforms, particularly privatization, has been disappointing. The authorities request waivers for three structural performance criteria on the basis of corrective actions concerning privatization policies in the cotton, telecommunications, and banking sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet